Diseño electromecánico de mano robótica con características funcionales para la comunicación dactilológica del abecedario y números dígitos en niños y niñas con discapacidad auditiva. - Hernández Ochoa, Luis David (2018)
In this research work the construction of a robotic hand is detailed to allow the communication of the alphabet and digit numbers in children with hearing disabilities. Considering the limited investment in technology to institutions in our country. It makes difficult to explain this type of communication in a didactic manner. They deal with the theoretical foundations that served as the basis of the research in an orderly and systematic way which allow to reach the objective of the project. The robotic hand is elaborated through the analysis of material resistance, machining times, the dimensioning through the logic of structured calculations, the communication through logic of programming and control for an adequate functionality of the didactic material.